1981
DOI: 10.1017/s0003356100031652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plane of nutrition and season of birth on the age and body weight at puberty of British Friesian heifers

Abstract: ABSTRACT1. Four groups of British Friesian heifers born in April (no. = 30), July (no. = 29), October (no. = 30) 1977 and January 1978 (no. =27) were allocated to one of six treatments (planes of nutrition) at a mean age of 91 days. From 91 to 365 days of age heifers on treatments 1 to 5 were given individually, according to body weight, a proprietary pellet to 126 days of age, and thereafter a diet of dried lucerne and barley. Heifers on treatments 1 and 2 were fed at the same rate whereas heifers on treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In the main this variation has little effect on W P , so that there appears to be a minimum, or critical, weight for the attainment of puberty, and the variation of growth consequently affects A P , the faster-growing individuals reaching puberty earlier. This relationship has been found, for example, in cattle by Crichton, Aitken & Boyne (1959), Dalton et al (1980), Little et al (1981); in rats by Wilen & Naftolin (1978); in chickens by Soller et al (1982); and in man (i.e. girls) by Frisch (1972).…”
Section: Discussionmentioning
confidence: 81%
“…In the main this variation has little effect on W P , so that there appears to be a minimum, or critical, weight for the attainment of puberty, and the variation of growth consequently affects A P , the faster-growing individuals reaching puberty earlier. This relationship has been found, for example, in cattle by Crichton, Aitken & Boyne (1959), Dalton et al (1980), Little et al (1981); in rats by Wilen & Naftolin (1978); in chickens by Soller et al (1982); and in man (i.e. girls) by Frisch (1972).…”
Section: Discussionmentioning
confidence: 81%
“…Enright et al (1995) showed that a 16-h daylight regimen reduced the age of puberty in comparison with an 8-h daylight treatment and Petitclerc et al (1983) noted that heifers exposed to longday photoperiods had higher growth rates than those exposed to short photoperiods. Little et al (1981) reported that heifers born in spring (when daylight was increasing) were lighter and younger at puberty than those born during autumn (decreasing daylight length). A long-day photoperiod (16 v. 8 h of daylight) increased mammary parenchymal weight by 40% in peri-pubertal heifer and by 30% in post-pubertal heifer (Petitclerc et al, 1985).…”
Section: Nutritional Factorsmentioning
confidence: 99%
“…The mechanism through which season of birth may affect first oestrus (FE) is not yet well understood: it may be nutritional in the 'quality' of nutrients assimilated, particularly for grazing animals; it may be behavioural as the animals' activity level varies with season and the young females are in differing stages of development; or more probably a complex interaction among several basic determinants. The latter conclusion is supported by results from, particularly, Little et al (1981), and to a lesser degree by Menge, Mares, Tyler and Casida (1960) and Hawk, Tyler and Casida (1954). These studies, however, considered season a categorical phenomenon, and grouped heifers by season of birth for further statistical analysis.…”
Section: Methodsmentioning
confidence: 86%
“…Recent experiments with Friesian heifers, (Roy. Gillies, Perfitt andStobo, 1980 andLittle, Mallinson, Gibbons andRowlands, 1981) found a relationship between age at puberty and season of birth. Roy et al (1980) also found that the occurrence of puberty was associated with the lunar phase.…”
Section: Introductionmentioning
confidence: 98%